The economic exploitation of child workers in the United Kingdom. (February 2017) - Hobbs, Sandy; McKechnie, Jim; Simpson, Amanda
Minimum wages legislation in the United Kingdom applies to those aged 16 years or older. Evidence is presented that children believe that their wage levels should be 'fair'. On one hand, such views have emerged from focus groups of working children. On the other, various pressure groups representing young people are seeking to establish fair payment to child workers. It is argued that the government, trade unions and other bodies have failed to adequately address the protection of young workers.